Teaching Good Character in Early Childhood Education through Construction Activites and Dramatic Play - Romadona, Nur Faizah; Setiasih, Ocih; Syaodih, Ernawulan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Character values are believed to be solid roots in supporting the integrity of the nation and state. The collapse of a country is resulted by the weakening of the character's values in the life of the people. The Ministry of National Education implements character education at all levels of education, including in Early Childhood Education. Developing Childrenâ€s characters is an obligation on us all, including parents and teacher. Parents are the primary educators of character, but empirically research shows that all adults who have contact with their children need to contribute to such education, especially their childrenâ€™s teachers. School has more influence later than parenting because of parents are much more emotionally salient in the first years of life, and many children do not experience full or even paart-time schooling until they are three, four or five years of age, when many aspect of character are already developing. In kindergarten, teacher can develop some values of character through learning, such as construction activities in a group and dramatic play. Construction activities involves manipulating one or multiple elements of the play environmet to construct something new. Dramatic play can be defined as a type of play where children accept and assign roles, and then act them out. In dramatic play, children negotiate and refine their growing understanding by consulting with other children and the teacher. Therefore, through construction activities and dramatic play, teacher can develop some values character such as discipline, tolerance, self-confidence, self-reliance, creative, helping others, cooperation, responsibility, hard-working and leadership